The Impact of Transit-Oriented Development (TOD) on Retail Property Rental Value in Jakarta's Block M Area - Aisyah Aisyah (Publikasi Indonesia, 2024)
This study aims to analyze the impact of Transit-Oriented Development (TOD) development on the rental value of retail properties in the Blok M area, Jakarta. The background of this research is based on the increasing adoption of TOD as a solution to traffic congestion and increased accessibility in urban areas. This research uses a qualitative method with an approach to interviews, observations, and document analysis. The results of the study showed a significant increase in the rental value of retail properties after the implementation of TOD, especially in three main shopping centers: Blok M Square, Blok M Plaza, and Blok M Mall. The percentage increase in rental prices per year reaches an average of 15%. These findings show that TOD contributes positively to the increase in retail property value in areas with high accessibility. In conclusion, TOD has an important role in supporting the economic growth of urban areas through increasing the value of retail properties.